Social support for families raising children with autism spectrum disorders (Mokslo taikomieji tyrimai / Applied Research, 2023)
The article reviews the issues the families raising children with Autism Spectrum Disorders encounter and the assistance available. The theoretical part presents the concept of Autism Spectrum Disorders and reviews the legal acts regulating family support and the need for social worker’s assistance for those families. The disorder usually manifests itself in early childhood, but the symptoms of autism can also appear later when social norms exceed the individual’s capabilities. Currently, there is no cure for Autism Spectrum Disorders, but various scientific studies show that it can be facilitated with various treatments.The research data show that after the child’s diagnosis, families received various social support; they were provided with the child’s disability and care money, sanatorium treatment, speech therapist services, special kindergarten education services, and psychologist services.It has also been determined that parents often face problems, such as financial difficulties, disturbed life rhythm, changed family functions, changes in family relationships, stress, and anxiety. It has been revealed that families raising children with Autism Spectrum Disorders lack free psychological counselling, greater financial support and information about autism spectrum disorder in one place. Parents often cannot find work because employers do not create favourable conditions allowing them to align parents’ working hours to the working hours of the child’s education institution. Parents of children with Autism Spectrum Disorders face social rejection and bullying and lack qualified professionals and the social support necessary. The research participants revealed a particular shortage of social workers’ services, organisation of children’s occupation, free therapy options, temporary respite services, and qualified specialists who would be ready to work with children with Autism Spectrum Disorders.
Keywords: autism spectrum disorders; child autism; atypical autism; asperger’s syndrome